Improvement of asphalt mixture performance with glass macro-fibers - Morea, Francisco (2018)
Cracking is a common failure in concrete asphalt mixtures due to fatigue and low temperatures. For centuries fibers have been used to reinforce materials and short and long fibers have extensive use in Portland cement concrete to control cracking and provide residual capacity. In the field of flexural pavements, fibers are commonly used in mixtures like stone mastic asphalt to increase the asphalt content that this mixture requires without binder drain down. Although many works show the reinforcement of asphalt mixtures with short fibers, there is a lack of information about the design and performance of asphalt mixtures incorporating macrofibers. This work explores the use of glass macrofibers in asphalt concrete mixtures. Improvements in fracture behavior at low to medium temperatures were found and macrofibers increased the first peak fracture stress and gave higher residual stress capacity. Additionally, rutting behavior was significantly improved by the addition of fibers reaching up to 50% reduction in permanent deformation with respect to mixtures without fibers.